Benzylic Functionalisation of Phenyl all‐cis‐2, 3, 5, 6‐Tetrafluorocyclohexane Provides Access to New Organofluorine Building Blocks. Issue 50 (31st July 2018) - Bykova, Tetiana; Al‐Maharik, Nawaf; Slawin, Alexandra M. Z.; Bühl, Michael; Lebl, Tomas; O'Hagan, David
Abstract: Selectively fluorinated hydrocarbons continue to attract attention for tuning pharmacokinetic properties in agrochemical and pharmaceutical discovery programmes. This study identifies benzylic bromination of phenyl all‐ cis ‐2, 3, 5, 6‐tetrafluorocyclohexane2 as a key reaction for accessing building blocks containing the all‐ cis ‐2, 3, 5, 6‐tetrafluorocyclohexane ring system. These cyclohexanes are of interest as the fluorines are only on one face of the cyclohexane, and this imparts an unusual polar aspect, very different to an otherwise hydrophobic cyclohexane. Ritter type reactions of benzyl bromide4 with DMF and acetonitrile generated the corresponding benzyl alcohol6 and benzylacetamide7 respectively. Benzylacetamide7 was hydrolysed to benzyl amine8 and syn ‐amino‐alcohol9, and separately the phenyl ring was oxidatively cleaved to furnish carboxylic acid acetamide10, which after hydrolysis gave the tetrafluorocyclohexyl amino acid11 . A trans ‐halogenation of benzylbromide4 with AgF2 gave benzyl fluoride13 . Oxidative cleavage of the aryl ring then gave pentafluorocyclohexyl carboxylic acid14 . This carboxylic acid was readily converted to amides23 –26 and the preferred conformations of these α‐fluoroamides were explored by DFT, X‐ray structure and 1 H– 19 F HOESY NMR analysis. Abstract : Selective fluorination : The access to building blocks with an all‐ cis ‐2, 3, 5, 6‐tetrafluorocyclohexane ring system is described. The fluorine substituents are only on one face of the cyclohexane ring; this imparts an unusual polar aspect, very different to an otherwise hydrophobic cyclohexane.